Indicadores ambientais para as comunidades que sustentam a agricultura (CSA) em São Paulo e agricultura solidária (SoLaWi) na Alemanha - Joana Ortega de Lima Amorim; Marta Cristina Marjotta-Maistro (Confins)
Our history shows a change in the patterns of knowledge and technologies applied in agriculture. Seeking to minimize the negative impacts generated by the "green revolution", organic and agroecological production practices have emerged, which also encompass concepts of family farming, solidarity economy and short marketing circuits in Brazil and Europe. The studies on CSA in Brazil are recent and there is a demand for guidance in search of their establishment as a sustainable option for agriculture. In this sense we chose SoLaWi - Solidariche Landwirtschaften (Solidarity Agriculture) in Germany as a parallel for the development of this work. The objective of this work is to analyse the environmental aspects that constitute the practices and relationships of SoLaWi and CSA, building qualitative indicators. The research was qualitative with primary data and based on the critical communicative methodology and complemented by content analysis and document analysis. From the data were created exclusionary and transformative indicators and it was observed that the CSA act strengthening agroecology in Germany and Brazil. The indicators of the environmental aspects of the communities are the search for biodiversity, soil preservation and health of people and ecosystems, encountering limitations in soil conservation and access to land. Future studies on the process of community formation and construction in the Latin American context are indicated, looking for capacity building of farmers and members for management and investment in critical education of members through public policies.